(3GdhWfjI gi GdMd (B/s - (3YHO Gdedc, CfhQs ((3GdbGgQI (B:s (3ecJHI GdTQhb GdOhdjI,s, 2007)
(3jLeY GdeDda ai gPG GdcJGH CMGOjK Yf bdhH CMHJ eUQ hYjhf PQaJ OehYgG Ydi eUQ hCQhGM UYOJ Edi GdSeGA TgjOI MH eUQ jHMK Yf SHH dMGdI GdJhgGf h GdJZjjH GdMGdjI hjbJQM MdhdgG jHMQ ai GdJGQjN GdbOje hjYGUQ GdCSGe GdMGdjI hjJSGAd eGPG MOK ddeUQjjf (B.. (3jJGHY GdEYdGe hOhQg hhSGFdg GdeJYOOI hQhGOg efP GdHOGjI(B. (3jSJQSd ai CacGQg Ydi UaMGJ gPG GdcJGH HGMKkG Yf hai GdLHgI GdhWfjI hGdQDjI GdeUQjI(B.s
(3GdHMK aj CUhd eUQ (B-- (3JZjjH eUQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B625-630.s
Keywords: (3GdbhejIs -- (3eUQs -- (3JGQjNs -- (3bQf (B20.s; (3eUQs -- (3SjGSI hMcheIs -- (3bQf (B20.s